Decline of Measles-Specific Immunoglobulin M Antibodies after Primary Measles, Mumps, and Rubella Vaccination - Helfand, Rita F. (American Society for Microbiology, 1998)
Detection of measles-specific immunoglobulin M (IgM) has become the standard diagnostic method for laboratory confirmation of measles. In outbreaks, the interpretation of an IgM-positive result can be complicated when persons with suspected measles receive a dose of measles vaccine as part of outbreak control measures. This investigation evaluated the decay of measles-specific IgM antibodies 1 to 4 months after primary vaccination with measles, mumps, and rubella vaccine (MMRII). Serum samples were obtained from 536 infants vaccinated when they were 15 months old as part of a study to assess primary and secondary measles vaccine failure. Sixty serum specimens per week were selected from specimens collected between 4 and 9 weeks after MMRII vaccination; all 176 available serum specimens collected between 10 and ≥16 weeks were included. Specimens were tested for the presence of measles-specific IgM by an antibody-capture enzyme immunoassay. The proportion of IgM-positive specimens dropped from 73% at 4 weeks after vaccination to 52% at 5 weeks after vaccination and then declined to 7% by 8 weeks after vaccination. Less than 10% of children remained IgM positive between 9 and 11 weeks. An IgM-negative result helps rule out the diagnosis of measles in a person with suspected infection and a history of recent vaccination. The interpretation of a positive IgM result from a person with a clinically suspected case of measles and a recent history of measles vaccination (especially within 8 weeks) is problematic, and the diagnosis of measles should be based on epidemiologic linkage to a confirmed case or on detection of wild-type measles virus.